Imposing Sanctions Against States and Violation Of Freedom Of Mass Media: The Case Of Iran - Shahbazi, Aramesh (Indonesian Journal of International Law, 2017)
Thorough U.S. and E.U sanctions that ban the export of goods and services to Iran remain largely obsolete in recognizing how communications can benefit both the civilian population and serve broader Western States foreign policy goals against the mentioned state. Recent sanction against more than 20 TV and radio channels was indeed just an attempt by the West against Iranian media. It was a flagrant violation of freedom of speech and in contrast to the free flow of information by satellite providers as Eutelsat SA and Intelsat SA which stopped the broadcast of several Iranian satellite channels in October 2012. Because of the International recognition of dignity, equality and autonomy of all people that led to formulation of fundamental rights, particularly with regard to freedom of expression and access to information and by correlation existed between the right to express and freedom of all kinds of mass media; in this article we would examine the case of recent sanctions against Iran. It seems clear that the sanctions are both the violation of the human rights values and also contrary to the fundamental principles of democracy, International Co-operations and in contrast with object and purpose of International Telecommunication Union.